2008
DOI: 10.1038/leu.2008.239
|View full text |Cite
|
Sign up to set email alerts
|

Noxa upregulation is associated with apoptosis of chronic lymphocytic leukemia cells induced by hyperforin but not flavopiridol

Abstract: Noxa upregulation is associated with apoptosis of chronic lymphocytic leukemia cells induced by hyperforin but not flavopiridol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…3A. As expected (15), flavopiridol-induced PARP-1 and p27 cleavages were associated with a strong Mcl-1 inhibition, a slight Bcl-2 cleavage and no stimulatory effect on Noxa levels. As also expected (15), hyperforin elicited PARP-1, p27 kip1 and Bcl-2 cleavages to a lesser extent than flavopiridol, did not inhibit Mcl-1 but strongly enhanced Noxa levels.…”
Section: M2yn Treatment Stimulates Noxa Expression In Cll Cellsmentioning
confidence: 50%
See 3 more Smart Citations
“…3A. As expected (15), flavopiridol-induced PARP-1 and p27 cleavages were associated with a strong Mcl-1 inhibition, a slight Bcl-2 cleavage and no stimulatory effect on Noxa levels. As also expected (15), hyperforin elicited PARP-1, p27 kip1 and Bcl-2 cleavages to a lesser extent than flavopiridol, did not inhibit Mcl-1 but strongly enhanced Noxa levels.…”
Section: M2yn Treatment Stimulates Noxa Expression In Cll Cellsmentioning
confidence: 50%
“…Consequently, the mechanism of action of M2Yn is different from that of flavopiridol and other plant-derived compounds acting through downregulation of antiapoptotic proteins including Mcl-1 (12,13). By upregulating the proapoptotic Noxa, M2Yn employs a mechanism shared by hyperforin, proteasome and HDAC inhibitors (15,17,18,32). This effect appears to result from a regulation at the protein level, as suggested by the ability of M2Yn to inhibit proteasomal activity in CLL cells, as do proteasome inhibitors (17) and hyperforin (Zaher et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most CLL cell apoptosis inducers, hyperforin triggers the caspasedependent mitochondrial pathway (19) but the molecular mechanisms allowing the liberation of apoptogenic factors from mitochondria are not elucidated. In a preliminary study, we found that Noxa protein is upregulated during apoptosis of CLL cells induced by hyperforin but not flavopiridol (23 In the present study, we first characterized this Noxa upregulation and then provided evidence favoring that Noxa is involved in the mechanism of action of the phloroglucinol through interaction with Mcl-1, displacement of the proapoptotic protein Bak from its complex with Mcl-1 and Bak activation, responsible for mitochondrial membrane permeabilization. Our data thus strengthen the concept of targeting the BH3-only protein Noxa for CLL therapy.…”
Section: Introductionmentioning
confidence: 87%